2017
DOI: 10.2298/sarh160301031s
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic, histopathologic and biochemical evaluation of lycopene effects on renal ischemia reperfusion injury in rats

Abstract: Introduction/Objective. Medical protection of kidneys against ischemia reperfusion injury is very important. Many agents have been used for the protection of ischemia reperfusion renal tissue injury. We aimed to evaluate the radioprotective effect of lycopene on kidneys in ischemia reperfusion injury with histopathological, biochemical, and scintigraphic parameters. Methods. Twenty-one Wistar male albino rats were divided into the following three groups: lycopene, control, and sham group. In the lycopene group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…Generated products of MPO, chlorinating oxidants arriving from chlorides and H 2 O 2 , are able to cause cell damage by reacting with amino acids, proteins, carbohydrates, lipids, and nucleobases [ 32 ]. The application of both forms of lycopene statistically significant decreases MPO activity ( Table 4 ), which is in accordance with previous studies where it is shown that lycopene decreases MPO activity in the damaged kidney [ 33 , 34 ] and myocardial [ 35 ] and pancreatic [ 36 ] tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Generated products of MPO, chlorinating oxidants arriving from chlorides and H 2 O 2 , are able to cause cell damage by reacting with amino acids, proteins, carbohydrates, lipids, and nucleobases [ 32 ]. The application of both forms of lycopene statistically significant decreases MPO activity ( Table 4 ), which is in accordance with previous studies where it is shown that lycopene decreases MPO activity in the damaged kidney [ 33 , 34 ] and myocardial [ 35 ] and pancreatic [ 36 ] tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Kaya et al (31) used single dose lycopene in renal IR injury and when they examined the biochemical and histopathological parameters, they mentioned that lycopene administered before renal IR decreased renal injury. In a study they conducted on the effect of lycopene on renal IR injury, Sadic et al (6) observed that lycopene reduces histopathological findings. In our study, lycopene reduced apoptosis, tubular dilation, tubular epithelium degeneration, glomerular shrinkage, desquame epithelium and proteinaceous cast rates.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphnuclear leukocytes migrate to the tissue, causing the formation of endothelial damage and excessive reactive oxygen species (ROS). Endoplasmic reticulum is damaged, leading to autophagosome formation and thus cellular lysis (6,7). ROS formation caused by reperfusion after an ischemic attack plays an important role in the pathogenesis of acute ischemic renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…In urology practice, protection against I/R damage and preservation of present nephron capacity is important in partial nephrectomy applied commonly in the treatment of small RCCs and renal transplantation 5 . Many treatment options were presented in literature to minimize nephron damage to occur due to the renal ischemia/reperfusion occurring in urology practice.…”
Section: Introductionmentioning
confidence: 99%